Melanocytic aggregates with unique morphology associated with regression of basal cell carcinoma. (23rd November 2019) - Jackson, Christopher R.; Sriharan, Aravindhan; Momtahen, Shabnam; Seidel, Gregory D.; Felty, Cameron C.; Ruby, Kristen N.; Yan, Shaofeng
Abstract: Background: Spontaneous regression of basal cell carcinomas (BCC) is a well‐documented phenomenon. In practice, we have observed melanocytic aggregates associated with BCC at various stages of regression showing unique morphologic features. Methods: Fourteen cases featuring melanocytic aggregates were retrospectively identified through a pathology database search. Clinical and histopathologic features were systematically evaluated, and additional immunohistochemical studies were performed. Melanocyte density within tumor nodules was compared to a group of control BCCs. Results: All cases showed BCC at various stages of regression with associated melanocytic aggregates, as highlighted by Melan‐A and SOX10 immunostains. Three of 14 cases (21.4%) had only dermal melanocytic nests, while 11 (78.6%) had both junctional and dermal nests. The melanocytic aggregates all had similar asymmetrical architecture and lacked maturation. The melanocytes were small, uniform, bland, and had minimal cytoplasm. Their nuclei were overlapping and hyperchromatic, and had inconspicuous nucleoli. None of the melanocytic aggregates stained for BRAFV600E by immunohistochemistry. No patient developed a recurrent or metastatic melanocytic lesion (median follow‐up 42 months). Melanocyte density was higher in the case series than in the control BCCs ( P = 0.0008). Conclusion: We described the unique morphology of melanocytic aggregates associated with BCC regression.